Functional limitations and coping mechanisms of women aged 60 years and older with self-reported hand osteoarthritis - J. McIntyre; R.W.E. Joubert; S.S. Ramklass (South African Family Practice)
Background: Hand osteoarthritis (HOA) is common in older women who seem to cope with the associated limitations in hand function. The importance of identifying coping mechanisms within a local context might have implications for intervention, especially with the introduction of National Health Insurance.